2020
DOI: 10.1103/physrevb.101.214435
|View full text |Cite
|
Sign up to set email alerts
|

In situ control of the helical and skyrmion phases in Cu2OSeO3 using high-pressure helium gas up to 5 kbar

Abstract: We report a small-angle neutron scattering study of the helical and skyrmion lattice order in singlecrystal Cu 2 OSeO 3 under quasihydrostatic helium gas pressures up to 5 kbar. By using helium gas as the pressure-transmitting medium (PTM) we ensure pressure application with improved hydrostaticity at cryogenic temperatures compared with previous reports where liquid PTMs were used. For 5-kbar He gas pressure we observe modest changes of the ambient pressure phase diagram; the critical temperature T c changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…One of the most prominent representatives of skyrmion hosting materials is the insulating B20-type compound Cu 2 OSeO 3 . A wide range of experiments have been performed on this compound, ranging from small-angle neutron scattering (SANS) [ 13 15 ], AC susceptibility [ 16 18 ] to various Lorentz transmission electron microscopy (LTEM) studies [ 19 , 20 ]. Furthermore, its magnetoelectric coupling allows to control its magnetic textures by external electric fields using the emerging electric polarisation as a handle.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most prominent representatives of skyrmion hosting materials is the insulating B20-type compound Cu 2 OSeO 3 . A wide range of experiments have been performed on this compound, ranging from small-angle neutron scattering (SANS) [ 13 15 ], AC susceptibility [ 16 18 ] to various Lorentz transmission electron microscopy (LTEM) studies [ 19 , 20 ]. Furthermore, its magnetoelectric coupling allows to control its magnetic textures by external electric fields using the emerging electric polarisation as a handle.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been investigated to engineer the size and position of the skyrmion pocket, such as the application of electric fields [17][18][19], the application of uniaxial [20][21][22] and hydrostatic pressure [23][24][25][26][27], and the reduction of the sample dimensions into thin films [28]. In addition, it has been shown that it is possible to stabilize the skyrmion state over a wide temperature and field range via rapid field cooling (RFC) through the skyrmion pocket [17,18,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%